Recent Developments in Antioxidants from Natural Sources - Otero Fuertes, Paz; Fraga Corralga Corral, María (Biochemistry, 2023)
Plants, fruits, and vegetables contain antioxidants that can be used as nutraceuticals or pharmaceuticals due to their perceived ability to reduce the risk of developing certain chronic diseases. This book includes thirteen chapters that discuss potential sources of new antioxidants from the fruits of South America and the flora of African countries, how to improve the production of antioxidants and methods to ensure the quality of antioxidants from fresh fruits and vegetables.